The relationship of national character and ethnocultural worldview in modern Kazakh poetry - Erdembekov B. A., Sultangaliyeva O. K.,; O., Soylemez (Opción, 2020)
The article is devoted to the continuity of the national character and ethnocultural outlook in modern Kazakh poetry via comparative qualitative research methods. As a result, one of the important issues of literary science is the report of our spiritual treasures, which preserve and develop the national culture, national heritage, comprehensively absorb humanistic ideas coming from our ancestors, consonant with the moral interests of the people. In conclusion, Modern Kazakh lyrics are a model of literature that developed Kazakh poetry, showed its character, raised Kazakh literature to a new level in the years of independence.